Aplicação de checklist, avaliação higiênico-sanitária, treinamento e adequação de boas práticas de fabricação (BPF) em serviço de alimentação em Florianópolis/SC - (:unkn) unknown (Universidade Federal do Pampa, 2013)
Food safety is a current challenge that aims to provide food free of chemical, physical and biological agents that may endanger the health of consumers. The consumer preference for more convenient meals influenced the collective market power, and the growth of these services, food became more exposed to a range of microbial contamination associated with incorrect practices of handling and processing, increasing concern with foodborne illness (DTA's). This study aimed to assess the sanitary conditions of a food service establishment located in Florianópolis / SC, through the application of a checklist proposed by RN n º 003/2005, and adapt it to the standards set by legislation through the adaptation of good manufacturing practices (GMP's), as well as the application of an evaluation questionnaire on the knowledge level of the handlers to submit them to a training on GMP. After training and fitness GMP was held again the application checklist and questionnaire, revealing that there was an improvement in personal hygiene and food handling, because the handlers learned about good food handling practices, being aware of manipulating them with a lower risk of contamination, ensuring not only their own health, as health consumers. And according to the checklist of food services of NR 003/2005, you can sort the property in Group 1 (76% to 100% compliance with the items) because we obtained a percentage of 87, 71% attendance compliance. It may be noted that the suitability of GMP and training were of great value to the perception of errors that may be occurring during the preparation of food, showing that more training and assessments should be carried out, always accompanied by a trained professional to ensure they are provided safe and quality food.
Keywords: Segurança dos alimentos; Contaminação microbiana; Condições higiênico-sanitárias; Food safety; Microbial contamination; Sanitary conditions; CNPQ::CIENCIAS AGRARIAS